Conditional and hidden infinite-dimensional symmetries of wave equations - Yehorchenko , I. A.; Vorobyova, A. I. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.9We consider conditional and hidden symmetry of multidimensional wave equations that are generated by additional conditions. An additional condition that corresponds to the dilation operator generates an infinite-dimensional symmetry for the wave equation.